2021
DOI: 10.1108/ci-04-2021-0069
|View full text |Cite
|
Sign up to set email alerts
|

BIM-based mixed-reality application for bridge inspection and maintenance

Abstract: Purpose The purpose of this study is to develop a building information modelling (BIM)-based mixed reality (MR) application to enhance and facilitate the process of managing bridge inspection and maintenance works remotely from office. It aims to address the ineffective decision-making process on maintenance tasks from the conventional method which relies on documents and 2D drawings on visual inspection. This study targets two key issues: creating a BIM-based model for bridge inspection and maintenance; and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The authors of [ 130 ] presented a BIM-based application where HoloLens is used to improve and facilitate the management of bridge inspections and maintenance procedures from the office. The authors named the application HoloBridge.…”
Section: Extended Reality For Structural Condition Assessment Of Civi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [ 130 ] presented a BIM-based application where HoloLens is used to improve and facilitate the management of bridge inspections and maintenance procedures from the office. The authors named the application HoloBridge.…”
Section: Extended Reality For Structural Condition Assessment Of Civi...mentioning
confidence: 99%
“… ( a ) Damage visualization and ( b ) condition rating visualization of bridge structure in HoloLens [ 130 ]. …”
Section: Figurementioning
confidence: 99%
“…With the introduction of Microsoft HoloLens, the development of AR/MR-based inspection tools rapidly advanced as researchers realized that marker-based solutions were no longer necessary (Ali et al, 2020a;Loporcaro et al, 2019). Integrating BIM and AR/MR is also prominent in this area to facilitate information flow during the inspection process (Donghai et al, 2021;Kim and Olsen, 2021;Nguyen et al, 2021Nguyen et al, , 2020. Besides that, some researchers also demonstrated the benefits of deep learning techniques in inspection tasks (Saovana et al, 2020).…”
Section: Inspectionmentioning
confidence: 99%
“…Inspectors have the potential to use AR to collect, interact with, visualise, and analyse inspection data on-site and in the office. In a pilot study that developed a bridge inspection process using AR, Nguyen et al (2020) concluded that 'information communication, visualization and collaboration in inspection work' (Nguyen et al 2020, pg. 43) is improved by making data more naturally interactive through real-time modelling.…”
Section: Augmented Reality and Virtual Realitymentioning
confidence: 99%